Evaluation of Centre of Gravity of Four Wheeled Trailer - Dhingra, Devinder; Barnwal, P; Dhingra, H S; Kumar, Ashwani (Journal of Agricultural Engineering, 2005)
A four-wheeled trailer with flat platfonn was designed for fabrication of mobile agro-processing unit. The size of the trailer is 4270 mm x 2135 mm and its wheelbase is 2630mm. The location of the centre of gravity in longitudinal, transverse and vertical direction was determined by weighing method / technique. The total weight and the reaction on rear wheels were measured using a weighbridge. These reactions were used to locate the centre of gravity in longitudinal and transverse directions. The rear wheels were lifted and the net reaction on them was measured. The amount of weight transferred to the front wheels is dependent on the height of the centre of gravity. This concept was used to locate the height of the plane-containing centre of gravity. The centre of gravity was located with reference to the plane containing the wheel axles. It was observed to be 1139 mm behind front wheel axle, 618 mm above the wheel axles and midway (perpendicular to the axles) between the wheels.